Correlation between 18F‐THK5351 tau PET imaging and the progression of neuropathology and clinical signs in a mouse model. (December 2021) - Vegas‐Gomez, Laura; Edwards, George A; Hasan, Omar; Ruiz, Nazaret Gamez; Schulz, Jonathan; Soto, Claudio; Schulz, Paul E; Moreno‐Gonzalez, Ines
Abstract: Background: Several common neurodegenerative disorders are characterized by the intracellular accumulation of neurofibrillary tangles (NFTs), which are composed of hyperphosphorylated tau protein (ptau). In Alzheimer's disease (AD), NFTs are accompanied by extracellular amyloid‐beta (Aβ), but primary tauopathy disorders are marked by the accumulation of tau protein alone. Abnormal ptau leads to the formation of insoluble aggregates in tauopathies such as AD. Positron emission tomography (PET) imaging is a promising avenue that may identify tau aggregates in vivo cross‐sectionally and longitudinally in various dementia conditions. Method: In this study, tau transgenic P301S mice, from 6 to 12 months of age, were analyzed by longitudinal in vivo PET brain imaging utilizing the tau ligand [ 18 F]THK5351, as well as histological, biochemical, and behavioral characterization over time. Result: Our results demonstrate elevated in vivo [ 18 F]‐THK5351 PET signaling over time in transgenic P301S tau mice from 8 months that had a positive correlation with histological and biochemical tau changes, and motor, memory and learning impairment. Conclusion: This study indicates that [ 18 F]‐THK5351 may facilitate detection of aberrant tau aggregation and deposition in order to differentiate between tauopathies, gain insights into their underlying pathophysiologies, and to have a reliable biomarker to follow during treatment trials. This work was partially funded by Department of Defense Peer Reviewed Alzheimer's Research Program Convergence Science. Research Award grant AZ160106 and Alzheimer's Association New Investigator Research Grant NIRG‐394284 to IMG.